Validating GIC Modeling in the Spanish Power Grid by Differential Magnetometry - S. Marsal; J. M. Torta; J. J. Curto; V. Canillas‐Pérez; O. Cid; M. Ibañez; A. Marcuello (Space Weather)
Abstract A series of experiences and recommendations are presented concerning the derivation of geomagnetically induced currents (GIC) by use of the differential magnetometry method (DMM) under power lines. This indirect technique, intended to obtain observations to validate GIC models, is an alternative to measuring the current flow in the transformer neutrals. It is a non‐intrusive and autonomous technique, as the procedure does not depend on the grid operator. In contrast, the selection of suitable sites devoid of human interferences, the need for power to supply the magnetometer, the data acquisition and transmission system, along with the choice of the appropriate instrumentation are difficulties that make not just any site suitable for installation and often require costly solutions. We focus on the methodology followed to estimate the GIC flowing in several transmission lines of the Spanish power grid with the aim of validating our GIC models, and we share our experience on the installation of the measuring points. Uncertainty inherent in the DMM is assessed, showing that noise is the main handicap, although it can be minimized with appropriate filtering. According to such experience, on some occasions only total DC currents above a significant fraction of 1 A give magnetic signatures well above the noise level, so this figure can roughly be considered as the threshold limit for detection. The low solar activity, combined with the mid‐latitude condition of Spain, limited the significance of available recorded data, but we can already report and analyze the results for several minor geomagnetic storms.